Optimizing Waqf Management for Demographic Bonus in Indonesia - Dianidza Arodha; Ayman (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2021)
Indonesia will in the demographic bonus which has a good and bad impact on economic development. Either impacts, Central Bureau of Statistics (BPS) of Indonesia launched that the latest data stated the amount of unemployed per February 2019 declined. The existence of productive waqf gives a great prospect to solve the negative impact of demographic bonus in Indonesia. Until now, the Indonesian government actives to promote a productive waqf as an instrument of economic welfare. Despite having a high potency, it still has many obstacles in its realization, likes low literary about productive waqf, human resources, etc.. both of them, demographic bonus and waqf can be synergized. Therefore, this study tries to explain the implementation of a government productive waqf in Indonesia. This paper finds a waqf linked Sukuk and micro waqf bank are the big potency can synergy with millennial in demographic bonus in Indonesia.